Thirty years after Balbina Dam: Diversity and floristic composition of the downstream floodplain forest, Central Amazon, Brazil. Issue 8 (16th October 2019) - da Rocha, Maíra; de Assis, Rafael Leandro; Piedade, Maria Teresa Fernandez; Feitosa, Yuri Oliveira; Householder, John Ethan; Lobo, Guilherme de Sousa; Demarchi, Layon Oreste; Albuquerque, Bianca Weiss; Quaresma, Adriano Costa; Ramos, José Ferreira; Schöngart, Jochen; Wittmann, Florian
Abstract: The construction of hydroelectric dams causes changes in the diversity and floristic composition of floodplain forests due to the irregularity of the hydrological regime in rivers downstream from the dams. In the Amazon Basin, plans for the construction of dams are threatening the igapós, forests flooded by blackwater rivers. In these floodplains, the distribution of tree species is synchronized with periodic flood events of the topographic gradient. Previous studies on the Balbina Dam show an altered flood pulse downstream. This work discusses the potential long‐term impacts on the diversity and floristic composition of an igapó downstream of the dam (Uatumã River) and compares it with an area unaffected by the dam (Abacate River). An evaluation of the vegetation strata—adults, saplings, and seedlings—showed that for all strata, diversity was greater in the high igapó (higher topographies) in the Uatumã area. This may be due to the near‐total absence of flooding in the high igapó and to the extent of flooding in the low igapó (low topographies). Thus, in the Uatumã area, seeds of species typical of flooded areas cannot reach the high igapó by water and, thus, tend to be replaced by upland forest species (mainly seedlings). In the low igapó, the typical species have difficulty establishing. Therefore, the Uatumã vegetation forms two different communities, which does not occur in the Abacate area. These effects of the dam led to irreversible changes in the diversity and floristic composition across all strata throughout the entire topography in the downstream region.